STRATEGIC MANAGEMENT OF THE ENTERPRISE ON THE BASIS OF PORTFOLIO ANALYSIS - Podra, Olha; Petryshyn, Nataliia (European Science, 2024)
The chapter is devoted to the study of the peculiarities of the enterprise portfolio analysis. The key concepts and terms are defined, the key methods of portfolio analysis of an enterprise are analyzed, their advantages and disadvantages are determined.